Correlation Mineral Water Consumption and Hemoglobin Levels in Adolescent Girls - Putri, Gela Setya Ayu; Maolida, Nurul; Sukeksi, Andri (Poltekkes Kemenkes Tanjung Karang, 2024)
Anemia is a global health issue that affects people of all ages, particularly adolescent girls. Adolescent girls require nutritional intake, both from food and water. According to the balanced nutrition guidelines, people (particularly adolescents and adults) require 2000 liters (or eight glasses) of water daily. Most adolescent girls barely consider their water consumption. A lack of water in the body affects the balance of minerals (salt and sugar), disrupting regular metabolic processes such as hemoglobin (Hb) level regulation. This study investigates the correlation between adolescent girls' water consumption and hemoglobin levels. This quantitative study uses a cross-sectional design to collect variable data at a certain time. The study used blood with anti-coagulants EDTA from 30 adolescent girls from Universitas Muhammadiyah Semarang. The primary data for this study are water consumption and hemoglobin levels. Results of the research show that adolescent girls' water consumption was adequate (66.7%) and low (33.3%). The average Hb level among adolescent girls was 12.4 g/dL. Adequate water consumption resulted in 3 respondents with low Hb levels and 7 with normal Hb levels. In contrast, low water consumption resulted in 2 respondents with low Hb levels and 18 with normal Hb levels. The Rank-Spearman correlation test showed sig 0.177 (p>0.05). The study concluded that there was no correlation between adolescent girl water consumption and hemoglobin levels. Food fluid intake can compensate for a lack of water consumption.